Determination of Bitter Compounds in Hops – Effect of Crop Year and Hops Age - Krofta, Karel; Mikyška, Alexandr; Jurková, Marie; Moravcová, Lenka; Vondráčková, Petra (KVASNY PRUMYSL, 2017)
Our study is focused on mutual comparison of four methods of determination of alpha acids in hops (EBC 7.4, EBC 7.5, ČSN and EBC 7.7) and their application in evaluation of hops stored under different conditions. Furthermore, the results of the comparison of predicted and actual alpha acid values in the long-term monitoring of harvesting of three Czech hop varieties are discussed. The largest differences were found between the EBC 7.5 (LCV) and EBC 7.7 (HPLC) methods; the first method gives systematically higher results and the difference exponentially increases with the hop storage index (HIS) value. The difference in HSI in fresh hops is 10 – 15% rel. while the difference in older hops with HSI 0.6 – 0.7 is 25 – 45% rel. Pre-harvest prognosis and harvest estimate of alpha acids in the Saaz variety are in good agreement with the facts (kr = 0.93, kr = 0.95) and the same holds for the harvest estimation relation and the reality of the varieties Sládek and Premiant (kr = 0.93; 0.97).